1986
DOI: 10.1007/bf00181240
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus properties of the serotonin agonist MK 212

Abstract: In an attempt to clarify the role of 5-hydroxytryptamine (5-HT) in the discriminative stimulus properties of MK 212 (6-chloro-2[1-piperazinyl]pyrazine), male Sprague-Dawley rats were trained to discriminate 0.5 mg/kg of this compound from saline. While the putative 5-HT agonists fenfluramine and m-chlorophenylpiperazine (MCPP) mimicked MK 212 in a dose-related manner, d-lysergic acid diethylamide (LSD), 8-hydroxy-2(di-n-propylamino)tetralin (8-OHDPAT), 5-methoxy-N,N-dimethyltryptamine (5-MeODMT), quipazine, Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Neurochemical studies of MK 212 have demonstrated that this piperazine analog exhibits its highest affinity (K i Ϸ 32-490 nM) for 5-HT 2C R and displays full efficacy to stimulate the 5-HT 2C R (Kennett, 1993;Porter et al, 1999;Cussac et al, 2002). In vivo analyses indicate that systemic administration of MK 212 evokes hyperthermia and hypophagia (Clineschmidt, 1979), oral dyskinesias (Eberle-Wang et al, 1996), penile erections (Berendsen et al, 1990), hypomotility (Lucki et al, 1989), and discriminative stimulus effects (Cunningham et al, 1986), all of which are blocked preferentially by 5-HT 2C R antagonists. In contrast, MK 212 has a much lower affinity for 5-HT 2A R (K i Ϸ 17,400 nM; Kennett, 1993;Porter et al, 1999) and does not evoke behavioral effects consistent with an efficacy to stimulate 5-HT 2A R (e.g., Lucki et al, 1989;Fiorella et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Neurochemical studies of MK 212 have demonstrated that this piperazine analog exhibits its highest affinity (K i Ϸ 32-490 nM) for 5-HT 2C R and displays full efficacy to stimulate the 5-HT 2C R (Kennett, 1993;Porter et al, 1999;Cussac et al, 2002). In vivo analyses indicate that systemic administration of MK 212 evokes hyperthermia and hypophagia (Clineschmidt, 1979), oral dyskinesias (Eberle-Wang et al, 1996), penile erections (Berendsen et al, 1990), hypomotility (Lucki et al, 1989), and discriminative stimulus effects (Cunningham et al, 1986), all of which are blocked preferentially by 5-HT 2C R antagonists. In contrast, MK 212 has a much lower affinity for 5-HT 2A R (K i Ϸ 17,400 nM; Kennett, 1993;Porter et al, 1999) and does not evoke behavioral effects consistent with an efficacy to stimulate 5-HT 2A R (e.g., Lucki et al, 1989;Fiorella et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…All drugs were injected in a volume of 1 ml/kg. The doses of drugs were chosen based upon their functional selectivity at a particular 5-HT 2 R (Cunningham et al, 1986;RinaldiCarmona et al, 1992;Schreiber et al, 1995;Kennett et al, 1997;Gobert et al, 2000); the affinity profiles for each of the 5-HT 2 R ligands are presented in Table 1.…”
Section: Drugsmentioning
confidence: 99%
“…Thereafter, five of these pigeons were retrained to discriminate an injection of 1.0 mg/kg of MK212 from saline. This training dose was based on the potency of MK212 to produce discriminative stimulus in rats (Cunningham et al 1986) and to substitute for the discriminative stimulus effects of mCPP in rats (Fiorella et al 1995b;Gommans et al 1998). Two additional pigeons failed to acquire a threechoice discrimination among injections of 0.1 mg/kg methysergide, saline, and 1.0 mg/kg WAY-163,909 in another experiment and these pigeons were retrained to discriminate 1.0 mg/kg MK212 from saline.…”
Section: Discrimination Training and Testingmentioning
confidence: 99%
“…Drug discrimination procedures have been used previously to determine the mechanisms of action for a range of psychoactive drugs (Hayes and Kelly 1985;Negus and Fantegrossi 2008), distinguish low and high efficacy opioid agonists (Young et al 1992;Zhang et al 2000), and separate GABA inverse agonists from neutral antagonists (Leidenheimer and Schechter 1991;McMahon and France 2005;Rowan and Lucki 1992;Takada et al 1986). Previous operant drug discrimination studies have established 5-HT 2C receptor agonists such as MK212 (Cunningham et al 1986), mCPP (Callahan and Cunningham 1994;Fiorella et al 1995b;Gommans et al 1998), and R0 60-0175 (Dekeyne et al 1999) and antagonists such as pizotifen (Minnema et al 1984), mianserin (Kelley et al 1995), clozapine (Hoenicke et al 1992), and ketanserin (Smith et al 1995), as discriminative stimuli in rats, mice, or pigeons. The profiles of a 5-HT 2A receptor agonist, neutral antagonist, and inverse agonist were compared using drug discrimination procedures (Li et al 2009) but patterns of drug discrimination responding for 5-HT 2C receptor agonists, neutral antagonists, and inverse agonists have not been examined.…”
mentioning
confidence: 97%